2008
DOI: 10.1128/mcb.01754-07
|View full text |Cite
|
Sign up to set email alerts
|

Activator-to-Repressor Conversion of T-Box Transcription Factors by the Ripply Family of Groucho/TLE-Associated Mediators

Abstract: The T-box family of transcription factors, defined by a conserved DNA binding domain called the T-box, regulate various aspects of embryogenesis by activating and/or repressing downstream genes. In spite of the biological significance of the T-box proteins, how they regulate transcription remains to be elucidated. Here we show that the Groucho/TLE-associated protein Ripply converts T-box proteins from activators to repressors. In cultured cells, zebrafish Ripply1, an essential component in somite segmentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…The Bowline/ripply family proteins mediate interactions between Tbx6/ tbx24, which are transcriptional activators that are commonly required for somite segmentation program (Nikaido et al, 2002;Yasuhiko et al, 2006), and the transcriptional corepressors XGrg-4/Groucho Kawamura et al, 2008). At the end of somitogenesis, it is likely that this interaction results in the suppression of Tbx6/tbx24-dependent transcription of genes that are essential for the somite segmentation program.…”
Section: Identification and Characterization Of Novel Somitogenesis-rmentioning
confidence: 99%
“…The Bowline/ripply family proteins mediate interactions between Tbx6/ tbx24, which are transcriptional activators that are commonly required for somite segmentation program (Nikaido et al, 2002;Yasuhiko et al, 2006), and the transcriptional corepressors XGrg-4/Groucho Kawamura et al, 2008). At the end of somitogenesis, it is likely that this interaction results in the suppression of Tbx6/tbx24-dependent transcription of genes that are essential for the somite segmentation program.…”
Section: Identification and Characterization Of Novel Somitogenesis-rmentioning
confidence: 99%
“…5A). Moreover, the tetrapeptide FPVQ in the Ripply/BDLC region, which is essential for interactions with T-box proteins (Kawamura et al, 2008) was also completely conserved (Fig. 5A).…”
Section: Isolation and Characterization Of A Third Xenopus Bowline/ Rmentioning
confidence: 99%
“…We have previously shown that Bowline interacts with Tbx6 protein via the Ripply/BDLC domain and suppresses the transcriptional activity of Tbx6 . Similarly, in zebrafish, Ripply1 interacts with Tbx24, which is related to Tbx6, to suppress the transcriptional activity of Tbx24 (Kawamura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…68,69 We identified a chromosome 6q14.2 microduplication involving RIPPLY2 that incompletely segregates with talipes equinovarus over three generations. Furthermore, the RIPPLY family of proteins have previously been shown to regulate T-box transcription factors during embryogenesis, 70 suggesting a possible link to the PITX1-TBX4 pathway during limb development.…”
Section: Copy Number Analysis In Talipes Equinovarusmentioning
confidence: 99%